2015
DOI: 10.1108/tg-07-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in India: current state, challenges and opportunities

Abstract: Purpose-The purpose of this conceptual paper is to present the scope of telemedicine, current state of telemedicine in India, challenges in its diffusion and suggest the way forward for implementation of such initiatives. Design/methodology/approach-This is viewpoint article that is prepared based on authors' exposure and knowledge about research topic and the context. A number of appropriate and current citations have been utilised to illustrate current state on the topic as well as to support authors argumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 15 publications
0
54
0
Order By: Relevance
“…Telemedicine has been deployed or of interest in many regions including developed countries 4 and developing countries. 5,6 A wide range of medical services is currently provided via telemedicine such as telelaboratory service, telehealth education and ambulance. 7 The elderly normally experience several common health issues such as chronic health conditions, cognitive health and mental health which make ability to move or travel to hospital become more difficult, impractical or sometimes impossible.…”
Section: Current State Of Telemedicinementioning
confidence: 99%
“…Telemedicine has been deployed or of interest in many regions including developed countries 4 and developing countries. 5,6 A wide range of medical services is currently provided via telemedicine such as telelaboratory service, telehealth education and ambulance. 7 The elderly normally experience several common health issues such as chronic health conditions, cognitive health and mental health which make ability to move or travel to hospital become more difficult, impractical or sometimes impossible.…”
Section: Current State Of Telemedicinementioning
confidence: 99%
“…This often leads to varying standards and coverage offered by service providers, including the dangers of a decrease in quality of handling ethical and legal concerns to be ahead of the competition. 5,6 The cost of telemedicine services is practically the same as that of services performed in face-to-face interactions. There is no assurance of pay equality among in-person health care and telemedicine providers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, liability and potential issues such as negligence and malpractice will also have an impact on telemedicine. [5][6][7] Telemedicine provides several benefits such as improving access and quick patient engagement at a cheaper cost, but ethical and legal challenges need to be taken into account while implementing telemedicine programs. 8 For example, some countries have described prerequisites for getting an educated permission, especially for telemedicine, to make sure patients follow the privacy risks and essential techniques of telemedicine.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a range of studies, conducted in India and Pakistan regarding the adoption of ICT within the healthcare domain [25][26][27][28][29][30][31][32][33][34][35][36]. Chandwani, Dwivedi [37] suggested challenges in the adoption of telemedicine can be classified across policy, societal, institutional and medical infrastructural levels. Elder, Clarke [38] identified that the specifics of the local environment had to be acknowledged when conducting research on the adoption of ICT within healthcare, as each environment has its own unique challenges.…”
Section: Literature Reviewmentioning
confidence: 99%